Evolution of Proanthocyanidins During Grape Maturation, Winemaking, and Aging Process of Red Wines - Jordão, António (2019)
Grapes and wine native proanthocyanidins are oligomers and polymers of flavan-3-ols linked mainly by C4–C8 and/or C4–C6 bonds (B type). Proanthocyanidins play an important role in red wine sensorial properties contributing to the wine color and mouthfeel properties. As a result of different factors, such as grape variety, grape maturation and sanitary level, climatic conditions, viticultural practices, winemaking, stabilization technology and type of aging, there is a high range in the levels and composition of proanthocyanidins quantified in the different fractions of grape bunch and in the wines. During the wine aging, in particular for red wines, several changes in the wine phenolic compounds occur. In many cases this aging occurs in the presence of wood, in particular by the use of oak wood (barrels or alternative wood products). Indeed, the environment evolving inside oak barrels during the maturation of wines provides conditions for further reactions involving several wood compounds and wine phenolics, like proanthocyanidins and anthocyanins, with consequent chemical and sensory repercussions.